2021
DOI: 10.1016/j.trsl.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Long and short non-coding RNA and radiation response: a review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 122 publications
0
30
0
Order By: Relevance
“…Strategies targeting circulating biomarkers, such as ncRNAs, could provide a more convenient method to evaluate plaque stability in patients with coronary heart disease [15,138,139]. There are several advantages for ncRNA application in clinical trials.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Strategies targeting circulating biomarkers, such as ncRNAs, could provide a more convenient method to evaluate plaque stability in patients with coronary heart disease [15,138,139]. There are several advantages for ncRNA application in clinical trials.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Although research into non-coding RNAs has become a hot topic, it is still a long way from clinical application. Currently, the main limitations for clinical use of non-coding RNA are as follows: 1) ncRNAs are often dynamic in the circulatory system, and the samples collected from patients in a certain period of time only represent the expression status at that time (May et al, 2021). Therefore, continuous dynamic and standardized monitoring is essential if ncRNAs are to be used as biomarkers of increased risk of RSA; however, this will lead to an increase in the cost of treatment.…”
Section: Restrictions On the Use Of Non-coding Rna In Clinicmentioning
confidence: 99%
“…A recent literature survey of Salamini-Montemurri et al, has identified 215 lncRNAs being involved in OCs, of which for 157 there is experimental proof [8]. Apart from initiation, lncRNAs have been associated with many biological processes associated with metastasis [80], such as the immune response [73], radiation response [81], epithelial to mesenchymal transition (EMT) and stemness [82], cell-to-cell communication, and regulation of the microenvironment in which cells reside [77].…”
Section: The Role Of Lncrnas In Various Biological Processes Related To Ovarian Carcinogenesismentioning
confidence: 99%
“…In contrast, other lncRNAs, such as HOTAIR or TUG1, can increase radioresistance by sponging specific miRNAs. Expression of lncRNAs can also be used as biomarkers of radiation damage, as lncRNA TP53COR1, TUG1 and MEG3 have been found to be upregulated after radiation damage by multiple studies [81]. Increasing the radiation sensitivity of tumor cells or increasing radiation resistance in healthy tissues by targeting specific lncRNA targets could be a promising approach for the treatment of various cancers, including ROCs.…”
Section: The Role Of Lncrnas In Various Biological Processes Related To Ovarian Carcinogenesismentioning
confidence: 99%